D
Deleted member 4993
Guest
.We have now proven the two strategies produce the same answer of \(\displaystyle \dfrac{20}{3}\)
Looking at the 1st one.
\(\displaystyle \dfrac{x}{12} + \dfrac{x}{15} = 1\)
\(\displaystyle (60x)\dfrac{x}{12} + (60x)\dfrac{x}{15} = (60x)1\) Why are you multiplying by 60 x? The LCM of (12, 15, 1) is 60 - not 60 x.
\(\displaystyle \dfrac{60x^{2}}{12} + \dfrac{60x^{2}}{15} = 60x\)
\(\displaystyle 5x^{2} + 4x^{2} = 60x\)
\(\displaystyle 9x^{2} = 60x\)
\(\displaystyle \dfrac{9x^{2}}{x}= \dfrac{60x}{x}\)
\(\displaystyle 9x = 60\)
\(\displaystyle x = \dfrac{60}{9}\)
\(\displaystyle x = \dfrac{20}{3}\)
Looking at the 2nd one.
\(\displaystyle \dfrac{1}{12} + \dfrac{1}{15} = \dfrac{1}{x}\)
\(\displaystyle (60x)\dfrac{1}{12} + (60x)\dfrac{1}{15} = (60x)\dfrac{1}{x}\)
\(\displaystyle \dfrac{60x}{12} + \dfrac{60x}{15} = \dfrac{60x}{x}\)
\(\displaystyle 5x + 4x = 60\)
\(\displaystyle 9x = 60\)
\(\displaystyle x = \dfrac{60}{9}\)
\(\displaystyle x = \dfrac{20}{3}\)